Pediatric minor head trauma: do cranial CT scans change the therapeutic approach? (Clinics, 2016)
OBJECTIVES: 1) To verify clinical signs correlated with appropriate cranial computed tomography scan indications and changes in the therapeutic approach in pediatric minor head trauma scenarios. 2) To estimate the radiation exposure of computed tomography scans with low dose protocols in the context of trauma and the additional associated risk. METHODS: Investigators reviewed the medical records of all children with minor head trauma, which was defined as a Glasgow coma scale ≥13 at the time of admission to the emergency room, who underwent computed tomography scans during the years of 2013 and 2014. A change in the therapeutic approach was defined as a neurosurgical intervention performed within 30 days, hospitalization, >;12 hours of observation, or neuro-specialist evaluation. RESULTS: Of the 1006 children evaluated, 101 showed some abnormality on head computed tomography scans, including 49 who were hospitalized, 16 who remained under observation and 36 who were dismissed. No patient underwent neurosurgery. No statistically significant relationship was observed between patient age, time between trauma and admission, or signs/symptoms related to trauma and abnormal imaging results. A statistically significant relationship between abnormal image results and a fall higher than 1.0 meter was observed (p=0.044). The mean effective dose was 2.0 mSv (0.1 to 6.8 mSv), corresponding to an estimated additional cancer risk of 0.05%. CONCLUSION: A computed tomography scan after minor head injury in pediatric patients did not show clinically relevant abnormalities that could lead to neurosurgical indications. Patients who fell more than 1.0 m were more likely to have changes in imaging tests, although these changes did not require neurosurgical intervention; therefore, the use of computed tomography scans may be questioned in this group. The results support the trend of more careful indications for cranial computed tomography scans for children with minor head trauma.